Association of serum placental growth factor and pregnancy associated plasma protein A between 11 to 14 weeks and pre-eclampsia - Kumar, Namrata; Das, Vinita; Agrawal, Anjoo; Pandey, Amita; Agrawal, Smriti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Pre eclampsia complicates around 5-10% of pregnancies worldwide. Many countries in the world are far away of having interventions to predict and prevent preeclampsia. A number of biochemical, biophysical and sonographic parameters are emerging as a potential tool which can help us in a long way. This study was aimed to study association of biochemical markers of preeclampsia in early pregnancy with the development of preeclampsia. Methods: This cohort study was conducted over a period of one year in the Department of Obstetrics and Gynecology at King George’s Medical University, Lucknow. Results: Total number of women enrolled at 11-14 weeks were 56. The mean age of women enrolled was 28±4.2 years. Out of total 44.6% women were nulliparous. Mean crown rump length at testing was 60.55±11.26mm. There was a significant correlation between the levels of Placental growth factors and development of PE (p<0.01) and especially severe early onset disease, however we did not found a significant correlation between Pregnancy associated plasma protein and Preeclampsia. Conclusions: Placental growth factor is an emerging marker which could be incorporated in essential bundle of care at 11 to 14 weeks testing in order to enhance the detection rates of preeclampsia.